The relationship of uremic toxin indoxyl sulfate and intestinal elimination mechanisms in hemodialysis patients - Adéla Tomášová; Alena Tichá; Sylvie Dusilová Sulková; Roman Safránek; Petr Moučka; Marcela Chmelařová; Ivana Baranová; Helena Párová; Zora Nývltová; Karolína Štochlová; Vladimír Palička; Ladislava Pavlíková; et al. (Karger Publishers, 2022)
Introduction: High indoxyl sulfate (IS) concentration is a serious problem for patients with CKD increasing the risk of cardiovascular diseases and CKD progression. Thus, the methods of decreasing the toxin concentrations are highly desired. The study aimed to discover the role of selected intestine related factors on IS concentration. Methods: We evaluated the impact of ABCG2 and ABCC2 polymorphisms influencing activity and protein intake by normalized protein catabolic rate. Additionally, we examined the relation of IS and uric acid (UA), that can share common elimination transporters. A monocentric, prospective, open cohort pilot study was performed on 108 patients undergoing dialysis treatment. Results: The positive effect of residual diuresis on the reduction of IS levels was confirmed (p = 0.005). Also, an increase in IS depending on the dietary protein intake was confirmed (p = 0.040). No significant correlation between ABC gene polymorphisms was observed either, suggesting the negligible role of ABCG2 and ABCC2 in the elimination of IS in small bowel. The significant difference was observed for UA where ABCG2 421C>A (rs72552713) gene polymorphism was higher (505.3 µmol/L) in comparison with a wild type genotype (360.5 µmol/L). Discussion/ Conclusion: No evidence of bowel elimination pathway via ABCC2 and ABCG2 transporters was found in renal replacement therapy patients.